Analysis of Factors Affecting Foreign Direct Investment Mineral Mining Sector in IndonesiaPeriod 2009-2012 - Zeflin Angga; . Purwanto (International Conference On Law, Business and Governance (ICon-LBG), 2013)
Indonesia is a country with plenty of natural resource and recently Indonesia needs investment in the mining sector reached IDR 830 trillion by 2014 in the context of the Master Plan for the Acceleration and Expansion of Indonesias Economic Development (MP3EI). In order to reach target, the researcher analyzing the effect of export mining sector, exchange rate, interest rate on foreign direct invesment mining sector in Indonesia during 2009 - 2012. This research using quantiative analysis with secondary data. Quantitative analysis consists of classical assumption test, multiple regression analysis, hypothesis testing by T test and F test, and determination coefficient (R2) analysis. Hypothesis test using T test shows that partially exchange rate have significant influence on FDI mining sector in Indonesia, but export mining sector and interest rates not significant on FDI mining sector in Indonesia, with Î± = 5%. Export mining sector has a positive effect while exchange rate and interest rates have a negative effect to FDI mining sector in Indonesia. F test showed that all independent variable are adequate to test dependent variable, means that independent variable have a significant effect into dependent variable with F score is 7.844. Adjusted R2 is 0.323 shows that 32.3% can be explained by the independent variables (Export mining sector, Exchange rates, and Interest Rates), and the other 67.7% is explained by other causes outside the model.